Harmonization of economic policies and public debt in sub-Saharan African countries - (:unkn) unknown (My University, 2019)
The objective of this thesis is threefold. First, we link debt to the regional context governed by the convergence criteria. After comparing the situation of sub-Saharan African countries in general with that of the Regional Economic Communities, we analyze the relationship between public debt and economic growth and assess the relevance of the debt limitation criteria. We question the role of membership in a regional grouping in reducing the level of debt. In a second step, we conduct an analysis focused on the convergence and explosiveness of the debt, in order to suggest re-groupings basedon the level of indebtedness. In a third step, we apply innovative methods, initially used in the analysis of heart rates, DNA segmentation, neurons or cloud structure, to examine the debt problem. These methods, which have never before been applied to this problem, have enabled us to highlight important aspects of public debt in the regional context of sub-Saharan African countries. It thus appears that the limitation criteria in place in the RECs are well and truly justified. The heterogeneity even within these countries has led us to recommend groupings based on fiscal regulation and fiscal convergence.It is therefore possible to doubt the relevance of setting up a common or single policy at the continental level. All the more so since it is emphasized that debt thresholds are not fixed and depend on the specific characteristics of each country. Moreover, regional grouping should no longer be exclusively geographical but rather political. The application of the recent MF-DFA methodologyreveals that South Africa’s public debt is characterized by a long memory effect leading to a multifractal character.
Keywords: African Research